Being a PhD student in the age of COVID-19 - Elise Guest; Sarah McGinnis; Xingtan Cao; Rachelle Lee-Krueger; Golshan Mahjoub; Kelly McKie; Lauren Morse; Sima Neisary; Hembadoon Oguanobi; Monsurat Omobola Raji; Lanqing Qin; Daphne Varghese (Canadian Society for Studies in Education, 2021)
In March 2020, the University of Ottawa, like many other universities across Canada and the world, transitioned to online learning in response to the global COVID-19 pandemic. This shift resulted in confusion, anxiety, and uncertainty as students had to adjust their schedules, their study habits, and, for some, their living situation. Within the Faculty of Education, the 2019 PhD student cohort wondered how the shift to online learning would affect their work and their research. This paper outlines the experiences of 12 members of this cohort. By writing this paper, we hope to not only share our feelings with other scholars, but to validate the feelings of other students across Canada. Although this paper is intended for graduate students, we feel that the sentiments and experiences expressed here may also offer valuable insight for both University and College administration.